MALE IMAGES IN SHORT STORIES BY B. ERSKINE - Rybalka, Iryna (Літературний процес: методологія, імена, тенденції, 2019)
The author of the article offers an analysis of male images in the works of the famous British writer B. Erskine’s short stories published in the collection of story “Encounters». The analysed fiction texts have not been translated into Ukrainian yet. The study presents the attempt to use the gender research techniques to study literary problems. Using the classification of the male social patterns of behavior worked out by N. Zhadanova, we analyse the collection of stories “Encounters” and single six types of male images: “Knight-aristocrat”, “Gentleman”, “Mate”, “Romantic”, “Son”, “Father”. These types of masculine images are neither positive nor negative, they always combine both traits this adds some more realism. The male image of the type “Gentleman” prevails in the above-mentioned collection, the fact can be explained by the national and cultural traditions of the society, described in the stories. The vector of this study is promising in the multistudy researches, that recently become popular in humanitarian scientific practice. DOI: https://doi.org/10.28925/2412-2475.2019.1322